Prison motherhood of women with an alcohol problem - Matysiak‑Błaszczyk, Agata; Jankowiak, Barbara (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
The motherhood of women deprived of their liberty is an important social problem, as it affects not only the prisoner herself, but also her children and the whole family, and well as the mother’s functioning in a prison. This problem is particularly difficult, as it affects not only prisoners who are mothers but also mothers addicted to alcohol. In this situation, the number of factors affecting the child’s development and the challenges posed by the resocialization facility increases. The way in which help is provided in prisons should take into account both the welfare of the mother and of the child. The results of the conducted research indicate that contact with psychoactive substances has a different effect on women than on men, and that there are gender differences in the consequences of using and abusing psychoactive substances. Problems related to alcohol abuse are common among women deprived of their liberty and addicts of convicted mothers are increasing in the population of criminal women and girls. The basic goals of employees of Mother and Child Homes and Shelters is to teach women, who are in a situation of active motherhood at the time of imprisonment, the skills connected with the social role of the mother, both under the condition of social isolation and after release. It is also important to ensure their children’s safety and to provide conditions which allow their psychosocial and physical development, taking into account the limitations related to the specificity of being in a closed facility.